Fenomena Sosiologis Petani Pedesaan yang Terpinggirkan di Indonesia - Mohammad Wahed; Ririt Iriani Sri Setiawati; Kiki Asmara (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2020)
This research is a literature study regarding changes in the social phenomena of rural farmer communities in Indonesia, behavior patterns and social interaction systems, including changes in cultural norms, values ??and phenomena. The limited number of farmers is one of the reasons that underlie poverty.